Analisis Kinerja Portofolio Saham Menggunakan Metode Sharpe, Treynor dan Jensen : Studi Kasus Indeks LQ45 Di Bursa Efek Indonesia Periode 2019-2022 - Ruma, Zainal; Tawe, Amiruddin (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
The purpose of this study was to determine the optimal stock portfolio performance on the LQ45 stock index on the Indonesia Stock Exchange for the period February 2019- December 2022. The data analysis method uses a single index model to form an optimal portfolio and uses the Sharpe, Treynor, and Jensen index methods to assess performance stock portfolio. Based on the results of the analysis of optimal portfolio formation, it shows that out of 30 samples of LQ45 index stocks, 8 stocks were obtained which included optimal portfolio stocks, namely ERB values > C*, namely ADRO, ANTM, BBCA, BRPT, INCO, INDY, ITMG, & MEDC stocks. the results of the stock portfolio performance appraisal analysis show that of the three portfolio performance appraisal index methods, the calculation of stock performance analysis, the average value of the Sharpe method is 0.1241, while the treynor method is 0.0112, and the Jensen method is 0.0334. The highest performance of the third method is the Sharpe method with an average performance value of 0.1241. So the Sharpe method is the best performance method compared to the Treynor and Jensen methods. The higher the Sharpe index value, the better the performance of the stock portfolio.